Getting the best out of continuing education: some tips for practising librarians in Nigeria (2013)
This paper is on how practicing librarians in Nigeria can get the best out of the continuing education programmes made available to them. It defined continuing education, various types of continuing education programmes and the rationales for continuing education. Techniques at getting the best out of continuing education programmes, how to effectively implement knowledge gained from continuing education in the world of work and the sustainability of continuing education programmes were the major issues discussed by the paper. The paper concluded and made recommendations on how continuing education can be given its pride of place by library managements, institutional administrators, professional associations and regulatory bodies in the country.